Synthesis of silver nanoparticle synthesis from tea leaf (Camellia Sinensis)extract and study on its antimicrobial - Nurul Afiqah, Abdul Rahim (2012)
Current nanotechnology research uses a lot of chemicals, which are potential threat to both environment and public health.Therefore the need to find more environmental friendly procedures for the production of nanoparticles arises.This research is done in with the purpose of synthesizing silver nanoparticles from tea leaves while studying its antimicrobial properties on Gram positive and Gram positive bacteria.Tea leaves(Camellia sinensis) has been used because of its rich source of polyphenolic compounds used for the reduction and capping of silver nanoparticles,making it a complete green chemical route.The reduction process of Ag+ to Ag0 was observed by the change of colour from clear brown to milky grey.The reaction was followed by the characterization of the silver nanoparticles using UV-Vis,FTIR,TEM and XRD.An average particle size of 26 nm silver nanoparticles could be obtained using TEM.The antimicrobial activity was tested using agar well method and it is found that the antimicrobial activity is observed to be higher against Gram negative bacteria.As a result of the research,it is determined that local plants such as tea leaves is an alternative to a safer,more eco-friendly alternative of synthesizing silver nanoparticles.